2022
DOI: 10.1051/0004-6361/202141976
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up dust nucleation theory in oxygen-rich evolved stars

Abstract: Context. Aluminium oxide (alumina; Al2O3) is a promising candidate as a primary dust condensate in the atmospheres of oxygen-rich evolved stars. Therefore, alumina ‘seed’ particles might trigger the onset of stellar dust formation and of stellar mass loss in the wind. However, the formation of alumina dust grains is not well understood. Aims. We aim to shed light on the initial steps of cosmic dust formation (i.e. nucleation) in oxygen-rich environments via a quantum-chemical bottom-up approach. Methods. Start… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 116 publications
0
36
1
Order By: Relevance
“…We use here a model that we applied recently to circumstellar gas trajectories, including nonpulsating and pulsating outflows, for two late-type stars with a different evolutionary stage: a semi-regular (SRV) AGB star, and a Mira-type (MIRA) AGB star (Gobrecht et al 2022). In the present study, we use the gas trajectories of the MIRA model star in oxygen-rich conditions (C/O = 0.75), characterised by a total density of ngas = 4 ✁ 10 14 cm -3 and a temperature of 2000 K at the stellar surface.…”
Section: Numerical Modellingmentioning
confidence: 99%
“…We use here a model that we applied recently to circumstellar gas trajectories, including nonpulsating and pulsating outflows, for two late-type stars with a different evolutionary stage: a semi-regular (SRV) AGB star, and a Mira-type (MIRA) AGB star (Gobrecht et al 2022). In the present study, we use the gas trajectories of the MIRA model star in oxygen-rich conditions (C/O = 0.75), characterised by a total density of ngas = 4 ✁ 10 14 cm -3 and a temperature of 2000 K at the stellar surface.…”
Section: Numerical Modellingmentioning
confidence: 99%
“…Consider again the fiducial reaction (1). Based on quantum chemical calculations (Gobrecht et al, 2022), the chemical routes involved in the formation of the monomer and the dimer of corundum are shown in Figure 4. As this figure illustrates, AlO is the main aluminum-bearing species involved and extra oxygen that is required is provided by H 2 O and OH, where the latter is part of the (kinetic) H-H 2 -O-OH-H 2 O system.…”
Section: Thermodynamics Versus Kineticsmentioning
confidence: 99%
“…This can be modeled by following the Lagrangian trajectory of a gas parcel through its shock compression and heating and adiabatic expansion and cooling phases with a chemical kinetics network. This approach-pioneered by Cherchneff and coworkers (Cherchneff, 2006)-has now been applied to the formation of molecules and dust formation in oxygen-rich and carbon-rich AGB ejecta (Cherchneff, 2011(Cherchneff, , 2012Decin et al, 2008;Gobrecht et al, 2016Gobrecht et al, , 2022. Figure 7 shows abundances calculated after one complete pulsation as a function of distance and efficient cluster formation in the wind occurs already at one stellar radius.…”
Section: Thermodynamics Versus Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…One such reaction that is likely is on the surface of aluminum (Al 2 O 3 ) dust grains that are condensed in the inner CSE of evolved stars (dust acceleration zone ;Ziurys 2006) and in the center of dense interstellar clouds (Mangan et al 2021;Gobrecht et al 2022). Casarin et al performed a density functional theory (DFT) based chemisorption study of the interaction of CO with an Al 2 O 3 surface and found that the preferred orientation consists of the C atom reacting perpendicular with the surface to form a chemical bond (Casarin et al 2000).…”
Section: Introductionmentioning
confidence: 99%